Curriculum co-development to strengthen climate risk management capacity of Senegal’s agricultural extension - Hansen, James; Trzaska, Sylwia; Whitbread, Anthony M.; Worou, Nadine; Akinseye, Folorunso M.; Diop, Mbaye; Thiaw, Cheikh; Ndiaye, Diabel; Konte, Oumar; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Strengthening the capacity of next users – particularly the amalgam of actors who comprise Senegal’s pluralistic agricultural extension system – is a crucial part of the AICCRA strategy for benefitting millions of farmers with climate information services (CIS) and climate-smart agriculture (CSA). This brief describes an ongoing process to design, develop and implement a short curriculum to strengthen the capacity of Senegal’s extension and advisory service providers to incorporate CIS into their work with farmers and agropastoralists. By strengthening human and institutional capacity to understand, communicate and apply climate information at critical points within the agricultural system, this process aims to catalyze agricultural system transformation, enhance the welfare and resilience of Senegal’s farming population, and sustain the impacts of AICCRA intervention.